PERSPECTIVE: Representations of Islam and Muslims in Psychological Publications - Sheridan, L. P. (The international journal for the psychology of religion, 2004)
A review was conducted of 1,354 abstracts in the PsycINFO database containing the terms Islam, Muslim and/or Moslem. These were analyzed in terms of article type (e.g., empirical works), publication type (e.g., book), topic (e.g., health, education), tone toward Islam (i.e., positive, negative, balanced), place of publication (e.g., United States), and religious background of author (assessed on the basis of 1st author name). It was concluded that Islam remains the focus of only a small proportion of the total number of published works; that 19.9% of abstracts represented comments, advice, and observations rather than data-driven research; that 7.2% adopted a negative tone toward Islam (compared with 12.9% that were positive); and that few publications have investigated attitudes toward Muslim populations.